Deletion of autophagy-related gene 7 in dopaminergic neurons prevents their loss induced by MPTP. (17th December 2016) - Niu, Xue-Yuan; Huang, Hou-Ju; Zhang, Jin-Bao; Zhang, Chan; Chen, Wei-Guang; Sun, Chen-You; Ding, Yu-Qiang; Liao, Min
Highlights: Generation of Atg7 CKO mice with specific deletion of Atg7 in mDA neurons. Adult Atg7 CKO mice contain fewer TH-positive mDA neurons compared with age-matched controls. MPTP-induced loss of mDA neurons is not present in Atg7 CKO mice. Abstract: Parkinson's disease (PD) is a neurodegenerative disease caused by a gradual loss of midbrain dopaminergic (mDA) neurons in the substantia nigra pars compacta (SNpc) during aging. 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is one of the neurotoxins used widely to induce PD-like symptoms in PD animal models, including rodents and non-human primates. It has been reported that deletion of autophagy-related gene 7 (Atg7) in the brain results in a reduction of mDA neurons in adulthood. In this study, we used tyrosine hydroxylase (TH)-Cre mice to generate conditional knockout (CKO) mice with the specific deletion of Atg7 in mDA neurons. Consistent with previous reports, adult Atg7 CKO mice contained fewer TH-positive mDA neurons compared with wild-type (WT) controls. TH-expressing neurons containing puncta-like structures with p62 and ubiquitin immunoreactivity were observed in the midbrain of Atg7 CKO mice but were not detected in control mice. However, MPTP-induced loss of mDA neurons was not observed in Atg7 CKO mice. Our results indicate that Atg7-involved autophagy is required not only for the survival of mDA neurons in the mouse brain, but also for MPTP-induced mDA neuron degeneration.